Pengembangan Lembar Kerja Siswa (LKS) berbasis Problem Solving terhadap Kemampuan Pemecahan Masalah Siswa pada Materi Sistem Pernapasan Kelas VIII - Nisa, Khoirun; Iza, Nikmatul (Universitas Insan Budi Utomo, 2024)
Problem solving is a process of individual thinking in a directed manner to determine what to do in overcoming a problem. Problem solving skills will train students to be more active in learning, generating ideas for the problem solving process. This study aims to produce teaching materials in the form of Student Worksheets (LKS) based on problem solving for students' problem solving abilities in the respiratory system material. This type of research is a development research using the 4-D development model developed by Thiagarajan which consists of (four) stages that include defining, designing, developing, and disseminating. However, in this study, this development model was modified according to needs. The model developed in this study became 3 (three) stages by limiting it to the development stage. The data collection technique was carried out by distributing validation questionnaire sheets compiled in the creation of Student Worksheets (LKS) based on problem solving to obtain an assessment from the validator, which aims to test the feasibility by media experts and material experts. The results of the LKS developed are based on the assessment of material experts obtaining a score of 3.25 with very valid criteria and the results of the media expert assessment obtained a score of 3.35 with very valid criteria.